2014
DOI: 10.1007/s15010-014-0641-1
|View full text |Cite|
|
Sign up to set email alerts
|

Oxacillin-susceptible methicillin-resistant Staphylococcus aureus (OS-MRSA), a hidden resistant mechanism among clinically significant isolates in the Wessex region/UK

Abstract: There are still many unknowns regarding phenotypic and/or genetic characterization of the emerging OS-MRSA isolates in the UK and worldwide. Data regarding their epidemiology and optimal therapy for infection are limited and need further investigation not only in the UK, but also worldwide, as it is likely to have an impact on the empirical treatment of S. aureus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
2
30
1
1
Order By: Relevance
“…These results were not consistent with a similar study done in Nigeria that 25% of cases were resistant to amoxicillin-clavulanic acid and 23% to erythromycin [19]. The difference observed between resistance rate to cefoxitin (11/60), and frequency of mecA (36/60) was related to the spread of the cefoxitin/oxacillin susceptible mecA positive OS-MRSA isolates in healthy population consistent with previous studies [20,21].…”
Section: Discussioncontrasting
confidence: 71%
“…These results were not consistent with a similar study done in Nigeria that 25% of cases were resistant to amoxicillin-clavulanic acid and 23% to erythromycin [19]. The difference observed between resistance rate to cefoxitin (11/60), and frequency of mecA (36/60) was related to the spread of the cefoxitin/oxacillin susceptible mecA positive OS-MRSA isolates in healthy population consistent with previous studies [20,21].…”
Section: Discussioncontrasting
confidence: 71%
“…Vyletelova et al (2011a) confirmed 23 isolated strains as MRSA by the PCR method (mecA gene), but 25 strains were resistant to oxacillin by the disk diffusion method. Saeed et al (2014) also found six (1.2%) OS-MRSA isolates phenotypically identified and reported as MRSA by conventional methods, originated from human samples. The occurrence of OS-MRSA means a hidden resistant mechanism that can have the impact on the correct treatment of S. aureus infections.…”
Section: Discussionmentioning
confidence: 86%
“…The occurrence of OS-MRSA also raises concerns about optimal therapeutics to target infections. It is commonly believed that most OS-MRSA strains exhibit hetero-resistance to oxacillin, which results in treatment failure of β-lactam antibiotics [8]. Notably, mupirocin could lead to conversion of OS-MRSA from a heterogeneous into a highly homogeneous resistant phenotype [34].…”
Section: Optimized Detection Procedures For Os-mrsamentioning
confidence: 99%
“…organisms in S. aureus, such as oxacillin-susceptible MRSA (OS-MRSA), which carry mecA or mecC but show MIC of oxacillin in the susceptible range (≤2 mg/L), have been described worldwide over recent years [7][8][9][10]. However, the prevalence of OS-MRSA in Chinese hospitals was reported to be 1.6% (34 of 2068) only in a single study [10], limited study has investigated the characteristics of OS-MRSA currently prevalent within Chinese hospitals and offered insights into the management of this special group of MRSA for clinical laboratories.…”
mentioning
confidence: 99%
See 1 more Smart Citation